KOMITMEN ORGANISASI BERDAMPAK PADA KINERJA PEGAWAI DITINJAU DARI ASPEK DISIPLIN KERJA, DIKLAT DAN PROFESIONALISME - Iwan Dwi Cahyanto; Basuki Sri Rahayu (STIE St. Pignatelli Surakarta, 2021)
The purpose of the study was to determine, test and analyze empirically the effect of work discipline, training and professionalism on employee commitment and performance at DPMPTSP Karanganyar Regency. Sampling using the census technique of 35 respondents. Research data is primary data, namely data obtained directly from respondents. Data collection techniques using observation, questionnaires and documentation. The data analysis technique used instrument test, linearity test, hypothesis test, path analysis. The results showed that training and professionalism had a significant effect on commitment, while work discipline had no significant effect on commitment; work discipline, training, professionalism and commitment have a significant effect on performance. The F test results show that work discipline, training, professionalism and commitment have a significant effect on performance. The total R2 test results are 0.981, meaning that the performance variable is explained by work discipline, training, professionalism, and commitment of 98.1 %, the remaining 1.9 % is explained by other factors outside the research model. The results of the path analysis show that the direct path of work discipline to performance is the most dominant and most effective path to improve performance. The commitment intervening variable cannot mediate all independent variables on the dependent variable.